2018
DOI: 10.1371/journal.pone.0204745
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of intravesical recurrence of non-muscle-invasive bladder cancer by evaluation of intratumoral Foxp3+ T cells in the primary transurethral resection of bladder tumor specimens

Abstract: Patients with a history of non-muscle-invasive bladder cancer sometimes have recurrence of tumors after transurethral resection of bladder tumor treatment. To find factors related to the recurrence of non-muscle-invasive bladder cancer, we examined tissue specimens taken at transurethral resection of bladder tumor as an initial treatment. We revealed the association between prognosis of non-muscle-invasive bladder cancer and infiltration of Foxp3+ T cells that suppress anti-tumor immunity in 115 primary non-mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…To assess other candidate immune-suppressive cells that could be altered by IL-2c, we undertook initial studies of Tregs and myeloid-derived suppressor cells (MDSCs), both of which are detrimental in human BC 40 41 and we previously reported that Tregs affect MB49 BC growth in bladder more than lung. 42 In our studies of IL-2c mechanisms in ovarian cancer, we found that IL-2c induces fragile Tregs with reduced suppressive function which are identified by maintained FoxP3 expression, and upregulated IFN-γ, T-bet, and PD-1.…”
Section: Resultsmentioning
confidence: 99%
“…To assess other candidate immune-suppressive cells that could be altered by IL-2c, we undertook initial studies of Tregs and myeloid-derived suppressor cells (MDSCs), both of which are detrimental in human BC 40 41 and we previously reported that Tregs affect MB49 BC growth in bladder more than lung. 42 In our studies of IL-2c mechanisms in ovarian cancer, we found that IL-2c induces fragile Tregs with reduced suppressive function which are identified by maintained FoxP3 expression, and upregulated IFN-γ, T-bet, and PD-1.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, blocking IL-10 and TGFβ has been shown to reduce the induction of CD25+ve regulatory T cells in vitro by a bladder cancer cell line (26). Such Tregs are capable of suppressing immune responses to cancer, often through their suppression of cytotoxic T cells and constitute a significant percentage of TILs in bladder cancer- a median of 17% across samples in one study (99). However, a clear role for regulatory T cells in bladder cancer is unclear with some studies suggesting a positive correlation with clinical outcomes.…”
Section: Foxp3 Regulatory Cells and Th17 Helper T Cellsmentioning
confidence: 99%
“…However, numerous studies have found negative correlations between FoxP3 T regulatory cells and survival including one study of 115 cases of NMIBC which found an inverse correlation between FoxP3 cell frequency within the tumor (as % of CD3+ve cells) and recurrence-free survival (99). Additionally, higher FoxP3 infiltration in the stroma around the tumor was shown to predict a shorter recurrence free survival post-BCG treatment for NMIBC (102).…”
Section: Foxp3 Regulatory Cells and Th17 Helper T Cellsmentioning
confidence: 99%
“…Of those survived full-text assessment, 3 were excluded for not clearly describing staining methods and one study was excluded because there was only one research on CD4+ lymphocytes, which provided limited values. Finally 14 studies were enrolled in this metaanalysis and the study characteristics are shown in Table 1 (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). All studies investigated TILs by immunohistochemistry or hematoxylin-and eosin (H&E)-stained sections in paraffin-embedded tissue.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%